Determination of Micro Minerals of Several Species of Sea Urchins from Samboang Waters as Functional Food Candidates - Hartanti, Lucky; Warsidah; Helena, Shifa; Tahirah; Irwan (Jurnal Ilmiah Platax, 2024)
Functional foods are foods that can be consumed with additional health benefits beyond their basic function as an energy source. The search for food sources from the sea is increasing, with many discoveries of active compounds from marine organisms. This research aims to determine the micromineral content of iron (Fe), zinc (Zn), and iodine (I) in several species of sea urchins in the coastal waters of Samboang Bulukumba. The results of this research can be a basis for utilizing this biota as a functional food. This laboratory research uses micromineral measurement instruments, for example, Atomic Absorption Spectrophotometry (AAS) for Fe and Zn, while for iodine minerals using High Performed Liquid Chromatography (HPLC) instruments. In this study, 2 types of sea urchins were found which were identified as Diadema cytosum and Tripneustes gratilla. The results of measuring the water content and ash content of the gonads of the two sea urchins were 77.32% and 1.15% for Diadema cytosum and 72.22% and 2.09% for Tripneustes gratilla. The results of measuring the levels of micro minerals Fe, Zn, and Iodine were respectively 115.24 ppm, 31.44 ppm and 16.71 ppm for Diadema cytosum and 150.75 and 27.27 ppm 21.21 ppm for Tripneustes gratilla. Keywords: functional food, AAS, HPLC, Diadema cytosum, Tripneustes gratilla Abstrak Pangan fungsional adalah makanan yang dapat dikonsumsi dengan manfaat kesehatan tambahan di luar dari fungsi dasarnya sebagai sumber energi. Pencarian sumber pangan dari laut semakin meningkat, dengan banyaknya penemuan senyawa-senyawa aktif dari organisme laut. Penelitian ini bertujuan  menentukan kandungan mikro  mineral besi (Fe), seng (Zn) dan yodium (I) dalam beberapa spesies bulu babi di perairan pantai Samboang Bulukumba. Hasil penelitian ini dapat menjadi dasar dalam memanfaatkan biota tersebut sebagai pangan fungsional. Penelitian laboratorium ini menggunakan instrumen pengukuran mineral mikro misalnya dengan  penggunaan Atomic Absorption Spectrofotometry (AAS) untuk Fe dan Zn, sedangkan untuk mineral yodium menggunakan instrumen High Performed Liquid Chromatography (HPLC). Dalam penelitian ini ditemukan 2 jenis bulu babi yang teridentifikasi sebagai  Diadema sitosum dan Tripneustes gratilla. Hasil pengukuran kadar air dan kadar abu gonad kedua bulu babi tersebut  diperoleh 77.32% dan 1.15% untuk Diadema sitosum dan sebesar 72.22% dan 2.09% untuk Tripneustes gratilla.  Hasil pengukuran  kadar mineral mikro Fe,  Zn dan Yodium masing-masing adalah sebesar 115.24  ppm, 31.44 ppm dan 16.71ppm untuk Diadema sitosum dan 150.75 dan 27.27 ppm 21.21 ppm untuk Tripneustes gratilla. Kata kunci : pangan fungsional, AAS, HPLC, Diadema sitosum, Tripneustes gratilla